The perceived causes of the (assumed) mathematics problems in England and South Africa: A social media experiment - (:unkn) unknown (My University, 2015)
This paper presents an exploratory study, using a methodology based on the idea of building knowledge through the use of social media such as blogs, discussion forums and twitter. The study builds on work carried out in the UK, collecting and synthesising reports related to mathematics education, and from this developing research on the perceived causes of the (assumed) problems with mathematics education in the UK. It develops the research to take account of the South African context, and investigates the same question in this context. The results are compared, and findings include the fact that in both countries 'negative attitudes' towards mathematics are seen as a major cause. The paper concludes by reflecting on the methodology adopted.
Keywords: African Research